2008
DOI: 10.1128/cvi.00421-07
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Feline Monocyte-Derived Dendritic Cells Loaded with Internally Inactivated Virus as a Vaccine against Feline Immunodeficiency Virus

Abstract: Dendritic cells are the only antigen-presenting cells that can present exogenous antigens to both helper and cytolytic T cells and prime Th1-type or Th2-type cellular immune responses. Given their unique immune functions, dendritic cells are considered attractive "live adjuvants" for vaccination and immunotherapy against cancer and infectious diseases. The present study was carried out to assess whether the reinjection of autologous monocyte-derived dendritic cells loaded with an aldithriol-2-inactivated prima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 27 publications
(32 reference statements)
1
10
1
Order By: Relevance
“…Several studies have shown that human monocyte-derived DC infected with HIV have reduced ability to stimulate allogeneic and mitogen-stimulated lymphocyte proliferation in vitro (Macatonia et al, 1989; Knight et al, 1993; Knight et al, 1997; Fantuzzi et al, 2004; Granelli-Piperno et al, 2004; Shan et al, 2007). In contrast to our studies, Freer et al (2008) showed that in vitro infection of monocyte-derived DC with a clade A FIV-petaluma virus did not impair subsequent lymphocyte proliferation. Conflicting study results may be due to the viral strain used, DC source, or differences in duration of infection and warrants further investigation.…”
Section: Function During Fiv Infectioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Several studies have shown that human monocyte-derived DC infected with HIV have reduced ability to stimulate allogeneic and mitogen-stimulated lymphocyte proliferation in vitro (Macatonia et al, 1989; Knight et al, 1993; Knight et al, 1997; Fantuzzi et al, 2004; Granelli-Piperno et al, 2004; Shan et al, 2007). In contrast to our studies, Freer et al (2008) showed that in vitro infection of monocyte-derived DC with a clade A FIV-petaluma virus did not impair subsequent lymphocyte proliferation. Conflicting study results may be due to the viral strain used, DC source, or differences in duration of infection and warrants further investigation.…”
Section: Function During Fiv Infectioncontrasting
confidence: 99%
“…Reggeti et al (2008) found that immunization of cats with allogeneic BM-derived DC did not induce cross-protective immunity against FIV that had been propagated in the same cells in vitro . Freer et al (2008) evaluated the potential of feline monocyte-derived DC loaded with AT-2-inactivated virus to provide protective immunity. DC were generated from peripheral blood mononuclear cells cultured in autologous plasma with GM-CSF and IL-4, loaded with AT-2-inactivated FIV, and matured with LPS.…”
Section: The Potential For DC Therapy In Lentiviral Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, the repeated inoculation of paraformaldehyde-fixed FIV-infected MBM cells afforded marked protection (43)(44)(45)69). However, the use of similarly fixed FIV-infected autologous infected T lymphocytes or of viable dendritic cells loaded with inactivated FIV failed to protect or even aggravated homologous virus challenge (18,21), thus excluding the possibility that the key to the success of the approach tested here was merely the use of a cellular boost. The reasons for its efficacy may be several that are not mutually exclusive.…”
Section: Discussionmentioning
confidence: 82%
“…Peripheral blood CD4 and CD8 T lymphocytes were counted as previously described (18). Briefly, 30 l of heparinized blood was incubated with 3 l of anti-feline CD4-or CD8-phycoerythrin (clones vpg34 and vpg9, respectively; AbD Serotec, Raleigh, NC) on ice for 30 min.…”
mentioning
confidence: 99%